Pediatric Liver Transplant Survival in Alagille Syndrome Is Comparable to Biliary Atresia—A Linked Database Analysis. Issue 3 (9th August 2022) - Black, Katherine; Ziogas, Ioannis A.; Thurm, Cary; Hall, Matt; Hafberg, Einar; Alexopoulos, Sophoclis P.; Godown, Justin; Gillis, Lynette A.
Abstract : Objectives: This study aims to report liver transplantation (LT) outcomes and cardiac disease manifestations in children with Alagille Syndrome (ALGS) in a contemporary cohort. Methods: This project used a novel linkage between the Scientific Registry of Transplant Recipients and Pediatric Health Information System databases. All children ≤21 years undergoing a first LT were identified (2002–2018). The presence of ALGS was identified using Scientific Registry of Transplant Recipients diagnosis coding. Subjects with ALGS were age-matched 1:2 to LT recipients with biliary atresia (BA). The Kaplan-Meier method and log-rank test were used to compare patient and graft survival between groups. Results: A total of 156 LT recipients with ALGS were identified and matched to a control group of 312 LT recipients with BA. Children with ALGS were more likely to have an associated diagnosis of congenital heart disease (80.7% vs 16.4%; P = 0.001) compared with children with BA with 40 (25.6%) children with AGS requiring cardiac intervention (catheter or surgical) either before or after LT. Those patients with ALGS had a higher creatinine, laboratory MELD, and PELD scores before LT. No difference was observed regarding patient or graft survival between children with ALGS and children with BA ( P = 0.08 and P = 0.27, respectively). Conclusions: Despite increased rate of congenital heart defects and cardiac interventions, higher creatinine, and higher laboratory MELD/PELD scores at time of transplant, this study demonstrates that there is no difference in either patient or graft survival between patients with ALGS and BA.